Community lifestyle patterns and household electrical energy consumption behavior to reduce carbon emissions - Siregar, Wiedyana Verawaty; Hasibuan, Arnawan; Razif, Razif (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2021)
Indonesia is a gas emitting country which ranks 6th in the world with carbon dioxide emissions of 1.98 billion tons of emissions per year. According to data from the Ministry of Energy and Mineral Resources (ESDM), the household sector accounts for around 36 percent of total energy. Energy demand in the household sector is estimated to increase to 70.6 million in line with the increase in the number of households in 2025. Given the threat of climate change and environmental problems and strengthened by the increase in the number of public outreach, people today have more information and knowledge about carbon emissions. This study will investigate the impact of subjective factors on household carbon emissions and further explore the relationship between the impact of consumer lifestyle using household electrical appliances and awareness on household carbon emissions in Lhokseumawe and North Aceh. The purpose of this study is to provide empirical evidence of the influence of perception factors, learning factors, and attitude factors on people's behavior regarding awareness of the impact of carbon emissions. Sampling using nonprobability sampling method and the number of samples used in this study were 200 respondents. Data analysis in this study used multiple linear regression analysis, to see the influence of Perception, Learning and attitude factors on people's behavior regarding awareness of the impact of carbon emissions. The test results in this study indicate that the perception factor and the attitude factor have a positive and significant effect on people's behavior regarding awareness of the impact of carbon emissions, while the learning variable has no significant effect on community behavior regarding awareness of the impact of carbon emissions.